A Meta-Review of Servant Leadership: Construct, Correlates, and the Process - Chaudhry, Anjali; Cao, Xiaoyun; Liden, Robert C.; Point, Sébastien; Vidyarthi, Prajya R. (Journal of Comparative International Management)

(untitled) (Management Futures, 2021)
The goal of this article is to present qualitative and quantitative reviews of servant leadership literature since its formal inception in 1970. Summarizing previous studies, we theorized and explored issues concerning the conception and relevance of servant leadership, the merits of varied measurements, issues concerning construct dimensionality, and the potential effects of national culture on the relationship between servant leadership and its correlates. We developed theory to distinguish servant leadership from competing leadership theories of transformational leadership and leader-member exchange (LMX) theory and examined the direct and the incremental influence of servant leadership on individual and unit-level outcomes. To consolidate extant research and to guide future theory development we tested a mediational process model linking servant leadership to outcomes. Meta-analytic results supported distinctiveness of servant leadership, showed effects of servant leadership on individual-level and unit-level outcomes, and supported theorized mediating effects of trust and fairness perceptions in the relationship.